A One Ocean Fleet : the Atlantic and Canadian Naval Policy - Sokolsky, Joel (Cahiers de géographie du Québec, 1990)
From the beginnings of the Cold War until the present the Canadian Navy has been a one ocean fleet, postured primarily to supply anti-submarine warfare (ASW) forces to the North Atlantic Treaty Organization (NATO) in the Atlantic. Various plans, including the 1987 White Paper on defence, to give the Navy more balance in terms of its areas of operation, mix of forces and missions, have been largely unsuccessful. The main reason for this is that the NATO maritime role has been directly related to the long-standing Canadian foreign policy objective of participating in this multilateral Alliance. In addition, forces earmarked for NATO's Atlantic Command (ACLANT) could also be used for North American maritime roles in cooperation with the United States Navy (USN) and for non-military sovereignty protection tasks. Recent dramatic changes in the international security environment combined with domestic budgetary pressures are likely to result in a continuation of this Atlantic orientation in Canadian naval policy.